At the Altar of the Appellate Gods : Arguing before the US Supreme Court - Gochman, Lisa Sarnoff (Book collections on Project MUSE., 2022)
"Have you ever wondered what it's like to argue before the Supreme Court of the United States?In this poignant and compelling memoir, Lisa Sarnoff Gochman captures the terror, wonder, and joy of preparing for and arguing a landmark criminal case before the nine justices of the US Supreme Court in Washington, DC. At the Altar of the Appellate Gods traces the arc of a violent, racially motivated crime by white supremacist Charles C. Apprendi Jr. in rural Vineland, New Jersey, through the New Jersey state court system, and all the way up to the Supreme Court, where Gochman defended the constitutionality of New Jersey's Hate Crime Statute before a very hot bench. Gochman went head-to-head with Justice Antonin Scalia, fielded tough questions from Justice Ruth Bader Ginsburg, and strolled down memory lane with Justice Sandra Day O'Connor. Told with grace and humor, At the Altar of the Appellate Gods will interest anyone who is curious about the inner workings of our court system and what it is really like to bring a case before the highest court in the country." - Publisher